2020
DOI: 10.1002/adsc.202000761
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytical and Photochemical Generation of Imidoyl Radicals: Synthetic Applications

Abstract: In the last few decades, the development in the field of radical chemistry has gained great attention. The majority of these radical strategies mainly depend on the in situ generation of reactive radical species by employing radical initiators such as oxidants and metal salts or methods such as photocatalysis and electrochemistry etc. This review covers the literature on the generation of imidoyl radicals using photoredox catalysis. In the majority of the reactions, the spontaneity of the underlying SET transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…The tert ‐butoxyl radical abstracts the aldehyde hydrogen atom to provide the acyl radical A , and the acyl radical A undergoes decarbonylation to yield the alkyl radical B . Then, the addition of radical intermediate B to the biphenyl isocyanides 1 afforded the imidoyl radical C [11b] . Subsequently, the imidoyl radical C cyclized to the arene to form cyclized radical intermediate D .…”
Section: Resultsmentioning
confidence: 99%
“…The tert ‐butoxyl radical abstracts the aldehyde hydrogen atom to provide the acyl radical A , and the acyl radical A undergoes decarbonylation to yield the alkyl radical B . Then, the addition of radical intermediate B to the biphenyl isocyanides 1 afforded the imidoyl radical C [11b] . Subsequently, the imidoyl radical C cyclized to the arene to form cyclized radical intermediate D .…”
Section: Resultsmentioning
confidence: 99%
“…36 The crude material (reaction time: 48 h) was purified by column chromatography (n-hexane/ethyl acetate 96:4) to give the product as an offwhite amorphous solid (6.9 mg, 39% yield). 1 H NMR (400 MHz, CDCl 3 ): δ 7.29−7.25 (m, 2H), 6.85 (t, J = 7.3 Hz, 1H), 6.74 (d, J = 8.0 Hz, 2H), 6.38 (br s, −NH), 3.73 (s, 2H), 2.98 (s, 3H), 1.33 (s, 9H); 13 N-((3s,5s,7s)-Adamantan-1-yl)-2-(methyl(phenyl)amino)acetamide (23). The crude material (reaction time: 48 h) was purified by column chromatography (n-hexane/ethyl acetate 9:1) to give the product as an off-white solid (6.7 mg, 28% yield).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Recently, with the advent of the visible-light photocatalysis era, the somophile reactivity has been investigated in a plethora of transformations involving intramolecular cyclization of 2-isocyanobiphenyls and related analogues, ,, as well as in two- or multicomponent reactions leading to amides, keto-amides, and other interesting molecular scaffolds. More in detail, these processes involve the formation of an imidoyl radical intermediate upon the addition of a radical species to isocyanide (Figure c). The imidoyl radical, depending on the reaction conditions and the species involved, can meet different fates such as oxidation to nitrilium ions, α-fragmentation (α-FGM) to give back isocyanide and the radical species, β-fragmentation (β-FGM) to nitrile (Figure a), and intramolecular interception of a radical acceptor (e.g., phenyl ring in the ortho -position of 2-isocyanobiphenyl, Figure b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In addition, isocyanides can function as radical acceptors to generate imidoyl radicals, which are fascinating reaction intermediates and usually lead to the formation of nitrogen heterocycles via radical cascade reactions. 6 Another typical reaction of isocyanides is the insertion reaction including insertion into heteroatom–hydrogen bonds, carbon–halogen bonds, carbon–hydrogen bonds, and metal carbenes. 7 In particular, isocyanide insertion into N–H bonds is a representative insertion reaction of isocyanides and was initially developed in the presence of copper catalysts in 1966, 8 but since then only a few studies have been reported on this reaction.…”
Section: Introductionmentioning
confidence: 99%